The Effectual Approach in Born Global Firms: Current State of Research - Elena Pawęta (Entrepreneurial Business and Economics Review, 2016)
Objective: The aim of this paper is to systematise the existing research at the intersection of international entrepreneurship and effectuation theories and propose the future research directions in this area.